1991
DOI: 10.1111/j.2044-8260.1991.tb00942.x
|View full text |Cite
|
Sign up to set email alerts
|

Performance of long‐stay schizophrenics after drug withdrawal on matched immediate and delayed recall tasks

Abstract: Both anticholinergic and neuroleptic drugs were withdrawn from eight long-stay hospitalized chronic schizophrenics. These patients and normal controls were then tested on Calev, Venables & Monk's (1983) immediate and delayed matched recall tasks to evaluate their rate of forgetting of verbal well-encoded materials. The results showed rapid forgetting in schizophrenics. This finding suggests that a post-encoding deficit characterizes long-stay schizophrenics after drug withdrawal. Cognitive and brain pathologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 3 publications
1
9
0
Order By: Relevance
“…However, all schizophrenia spectrum patients who had positive symptoms had better immediate than delayed recall performance, as compared with normal controls. This replicates previous findings in schizophrenic patients [11][12][13], but it also adds some important information. Firstly, the present schizophrenic patients were not long hospitalized, and thus they differed from the patients reported to have rapid forgetting in the past.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…However, all schizophrenia spectrum patients who had positive symptoms had better immediate than delayed recall performance, as compared with normal controls. This replicates previous findings in schizophrenic patients [11][12][13], but it also adds some important information. Firstly, the present schizophrenic patients were not long hospitalized, and thus they differed from the patients reported to have rapid forgetting in the past.…”
Section: Discussionsupporting
confidence: 80%
“…Since previous research [11,12] has shown that raw and arcsintransformed data analyses produce very similar results when using these tasks, raw data were analyzed using analyses of variance, t tests and correlations. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…4, 5], and unlike shortstay patients show evidence of retention diffi culty, i.e. they show rapid forgetting [6,7], Dr. Avraham Calev …”
mentioning
confidence: 99%